Chemoradiotherapy in pancreatic carcinoma - Pathy Sushmita; Chander Subhash (Indian Journal of Medical and Paediatric Oncology)
Pancreatic cancer patients present late in their course and surgical resection as a modality of treatment is of limited value. Majority develop loco-regional failure and distant metastasis, therefore, adjuvant therapy comprising of radiotherapy and chemotherapy are useful treatment options to achieve higher loco-regional control. Specialized irradiation techniques like intra-operative radiotherapy that help to increase the total tumor dose have been used, however, controvertible survival benefit was observed. Various studies have shown improved median and overall survival with chemoradiotherapy for advanced unresectable pancreatic carcinoma. The role of new agents such as topoisomerase I inhibitors also needs further clinical investigations.